ICT Integration in Primary Class Rooms: Attitude and Concerns of Primary School Teachers of Kerala - Muneer, V.; Saleem, T. Mohamed (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The use of technology in the classroom improves student‘s motivation and attitude about themselves and about learning. For this technology needs to be effectively integrated into formal classroom teaching and learning conditions. In this study researchers studied the attitude of primary school teachers of kerala towards ICT integration in class room. 130 primary school teachers of Kerala were selected as the sample for the study. Data collected by using Attitude scale towards ICT integration and Questionnaire on problems of ICT Integration. Results of the study revealed that primary school teachers of Kerala posse‘s positive attitude towards ICT integration in class room. Study also analysed the different problems faced by the primary school teachers while integrating ICT in class room.